2021
DOI: 10.2147/cmar.s329687
|View full text |Cite
|
Sign up to set email alerts
|

A Survival Prediction Nomogram for Esophageal Squamous Cell Carcinoma Treated with Neoadjuvant Chemoradiotherapy Followed by Surgery

Abstract: Background: Neoadjuvant chemoradiotherapy (NCRT) followed by surgery is a component of the standard treatment for resectable locally advanced esophageal squamous cell carcinoma (ESCC), and the parameters for survival prediction are not clear yet. Our study aimed to construct a survival prediction nomogram for ESCC with NCRT followed by surgery. Methods: We analyzed hematological parameters and related-derivative indexes from 122 ESCC patients treated with NCRT followed by surgery. Univariate and multivariate C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 80 publications
0
10
0
Order By: Relevance
“…Nomograms based on traditional demographic characteristics (such as age, sex, and race) and clinicopathological features (such as TNM stage, tumor location, tumor size, tumor grade, depth of invasion, and number of metastases) only show a moderate performance ( 16 , 19 , 20 ). Some studies have incorporated the nutritional information and inflammatory profile of patients into the nomogram and successfully demonstrated that the developed nomogram has a better performance than the TNM staging system ( 6 , 21 , 22 ). In addition, other studies have incorporated genomic data, such as DNA methylation ( 23 ), long non-coding RNA ( 24 ), and autophagy-related gene data ( 25 ), into the nomogram and successfully shown that the developed nomogram has a better discrimination ability than the TNM staging system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nomograms based on traditional demographic characteristics (such as age, sex, and race) and clinicopathological features (such as TNM stage, tumor location, tumor size, tumor grade, depth of invasion, and number of metastases) only show a moderate performance ( 16 , 19 , 20 ). Some studies have incorporated the nutritional information and inflammatory profile of patients into the nomogram and successfully demonstrated that the developed nomogram has a better performance than the TNM staging system ( 6 , 21 , 22 ). In addition, other studies have incorporated genomic data, such as DNA methylation ( 23 ), long non-coding RNA ( 24 ), and autophagy-related gene data ( 25 ), into the nomogram and successfully shown that the developed nomogram has a better discrimination ability than the TNM staging system.…”
Section: Discussionmentioning
confidence: 99%
“…Even early-stage patients who have undergone surgery relapse after a period of time. More than 80% of patients die of metastasis and recurrence, and the overall 5-year survival rate of EC is 15–25% ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…It allows the three-dimensional distribution of optical probes in the focal area to be reconstructed 2,5 . Tumor, node and metastatic staging systems are commonly used in evaluating tumor development and staging 6,7 . For tumor staging by optical molecular technology, tumor spread can be seen as a multi-source problem.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, NCRT takes an unshakable position in comprehensive anti-tumor therapy. With the addition of adjuvant therapy, pathological TNM stage is seemingly not so reliable in predicting the prognosis of neoadjuvant therapy in contrast with surgery alone [7]. Thus, to help determine prognoses, the imaging and pathological approaches which aim to assess tumor regression were always regarded as important evaluation means [8].…”
Section: Introductionmentioning
confidence: 99%